Young adult with varicosities and recurrent lower gastrointestinal bleeding - Gandhi, Vidhyachandra V.; Gautam, Pratik; Pai, Nitin V.; Hegde, Sujai (International Surgery Journal, 2019)
A 30 years gentleman presented with anaemia since last ten years due to recurrent rectal bleeding. He has had multiple admissions with transfusions in the preceding 10 years without a clear clinical diagnosis. His physical examination revealed gross pallor, prominent veins on the lateral side of the left lower limb with minimal hypertrophy and a hemangiomatous patch over the left buttock. Colonoscopy revealed a few dilated tortuous submucosal vessels in the rectum and sigmoid colon. A MR angiogram showed absent left popliteal vein and angiomatous lesions in the rectum and sigmoid colon. He was diagnosed to have Klippel-Trenaunay syndrome with hemangiomata of the lower gastrointestinal tract causing bleeding. He underwent a low anterior resection with stapled anastomosis, which has effectively controlled his bleeding. Adults with gastrointestinal bleeding due to congenital venous malformations commonly have visible external stigmata, which are often pointers of rare syndromes.